UTILIZATION OF CASSAVA AS SUBSTITUTION FOR KEROSENE - Harie Satiyadi Jaya (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
Ethanol or ethyl alcohol C2H5OH, is a colorless liquid, insoluble in water, ether, acetone, benzene, and all organic solvents, and has a distinctive odor of alcohol. One of the most famous manufacture of ethanol is fermentation. Bioethanol can be obtained by means of fermenting cassava. This study was conducted to obtain bioethanol from cassava by fermentation using yeast tape. Variable used in this study is the ratio of yeast (80 g, 90 g, 100 g), the addition of nutrients NPK (10 g, 15 g, 20 g), and fermentation duration (10 days, 14 days, 18 days). In this study, the results showed that the addition of variable 90 gr yeast obtained the highest results of 5,33% v/v, for variable nutrient addition of 20 g of NPK obtained highest result of 4,98% v/v, while for variable fermentation duration obtained the highest yield in fermentation time of 14 days is 4,14% v/v dengan percent average error for variable yeast is 96,33%, for the nutrient variables is 96,66% , and for a fermentation duration variables of 97,24%, on a substrate fermentation using cassava with starch content of 21,6%.